Association Between Screen Time Duration and Attention- Deficit/Hyperactivity Disorder Symptoms Among Children Aged 4–6 Years - Adnan Faris Naufal; Anida Azkia Fitri; Arif Pristianto; Laura Kirana (Masters Program in Public Health, 2026)
Background: The rapid increase in screen time among children has raised urgent public health concerns due to its potential link with Attention- Deficit/ Hyperactivity Disorder (ADHD)-related symptoms. Emerging evidence suggests that excessive and early exposure to digital media may contribute to inattention, impulsivity, and behavioral dysregulation. This study aimed to examine the association between the duration of gadget use and ADHD symptoms in children aged 4–6 years. Subjects and Method: A cross-sectional study was conducted at four early childhood education institutions in Kartasura, Central Java, Indonesia. A total of 87 children aged 4–6 years were included. Screen time duration was assessed using a 7-day parent-reported observation sheet. ADHD symptoms were measured using the ADHD Rating Scale-5 (ADHDRS-5). The association between screen time duration and ADHD symptoms was analyzed using Pearson’s correlation test. Results: There was a statistically significant positive correlation between screen time duration and ADHD symptoms (r = 0.35; p = 0.001). Conclusion: Longer screen time duration is associated with higher levels of ADHD symptoms among children aged 4–6 years.